2017
DOI: 10.1186/s13058-017-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids induce production of reactive oxygen species/reactive nitrogen species and DNA damage through an iNOS mediated pathway in breast cancer

Abstract: BackgroundPsychological stress increases the circulating levels of the stress hormones cortisol and norepinephrine (NE). Chronic exposure to elevated stress hormones has been linked to a reduced response to chemotherapy through induction of DNA damage. We hypothesize that stress hormone signalling may induce DNA damage through the production of reactive oxygen species (ROS)/reactive nitrogen species (RNS) and interference in DNA repair processes, promoting tumourigenesis.MethodsBreast cancer cell lines were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 43 publications
7
96
0
Order By: Relevance
“…Analysis of the psychological index and BC risk has hinted at a positive correlation . Psychological stress increases the level of glucocorticoids, and reduces the ability to repair DNA damage by increasing the production of reactive oxygen species/reactive nitrogen species in BC . Irwin et al reported that psychological changes related to life events reduced the activity of NK cells .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the psychological index and BC risk has hinted at a positive correlation . Psychological stress increases the level of glucocorticoids, and reduces the ability to repair DNA damage by increasing the production of reactive oxygen species/reactive nitrogen species in BC . Irwin et al reported that psychological changes related to life events reduced the activity of NK cells .…”
Section: Discussionmentioning
confidence: 99%
“…Infection or chronic inflammation contributes to the occurrence of cancer mainly by leukocytes and immune cells in inflammatory lesions, which are activated by inflammation and produce ROS and reactive nitrogen species (RNS) [79,80]. ROS cause damage by oxidizing DNA (including point mutations, deletions, and gene reassortment), disrupting DNA repair, and posttranslationally modifying cancer proteins [81].…”
Section: Oxidative Stress and Tumorsmentioning
confidence: 99%
“…Several GR positive cancer cell lines, MCF-7 and MDA-MB-231 were incubated with cortisol and norepinephrine for 30minutes where controls included incubation with hydrogen peroxide. A comet assay assessed DNA damage and repair and Flaherty et al demonstrated that acute exposure to cortisol increased DNA damage and repair was reduced 35) . Numerous studies in mice as well as humans reveal significant differences in the cell's ability to repair DNA damage or to undergo apoptosis while under stress compared to cells with no stressful conditions [Glaser, 36,37,38,39) .…”
Section: Cortisol and Breast Cancer: Molecular Evidencementioning
confidence: 99%